Pengaruh Media Pembelajaran Quizlet Terhadap Penguasaan Kosakata Bahasa Jepang Siswa Kelas XI SMAN 8 Pekanbaru - Tasya Hendri Putri; Merri Silvia Basri; Dini Budiani (KIRYOKU, 2023)
This study aims is based on viewing the Japanese vocabulary’s knowledge of second grade student of SMAN 8 Pekanbaru, pre-using and post-using Quizlet as a learning media, also to review whether Quizlet as a learning media is effective for learning Japanese vocabulary. The population in this study were students of second grade of SMAN 8 Pekanbaru with sample of 33 students from class XI IPA 9 as the experimental class and 33 students from class XI IPA 8 as the control class. The results of this study are as seen in the results of the independent sample t test from the post-test value data, Sig(2-tailed) is 0.002 which shows that Quizlet as a learning media is effective for supporting Japanese vocabulary’s knowledge in second grade students of SMAN 8 Pekanbaru.